(untitled) (Annals of Medical Research, 2021)
Aim: The objective of this study was to research the relation between residual SYNTAX score and neutrophil/lymphocyte ratio in patients with ST segment elevation myocardial infarction (STEMI).Material and Methods: A total of 300 patients with STEMI were included from January 2015 to February 2020. Residual SYNTAX score (RSS) was calculated for each patient after primary percutaneous coronary intervention (PCI). RSS>8 was accepted as high RSS. Clinical and laboratory features of the patients including neutrophil/lymphocyte ratio were recorded. Results: 109 (36.3%) of the patients had RSS over 8 and classified as high RSS. In the high residual SYNTAX group, while the neutrophil count was higher (p0.001), the lymphocyte count was lower (p0.001) and the N / L ratio was statistically higher (p0.001). In terms of multivariate analysis, glucose [( p :0.023, OR: 1.005, 95% CI (1.001-1.009) ], CRP [( p: 0.033, OR: 1.018, 95% CI (1.001-1035)], culprit vessel [( p 0.001, OR: 3.437, 95% CI (1.741-6.786)] and N/L ratio [( p0.001,OR: 1.559, 95% CI (1.364-1.780) were independent predictors of high RSS. The threshold value of N/L ratio for RSS was calculated to be 4.50 [76.1 % sensitivity and 82.7 % specificity, AUC: 0.823, p0.001, 95% CI: 0.771-0.876].Conclusion: Neutrophil/ lymphocyte ratio is significantly associated with high residual SYNTAX score and also an independent predictor of coronary atherosclerotic burden after PCI.